Evaluation of Clinical and Sociodemographic Characteristics of the Children Dragged to Crime - Güler, Gülen; Sungur, Mehmet Ali; Kütük, Meryem Özlem (The Bulletin of Legal Medicine, 2018)
Objective: In the evaluation of children dragged to crime aged between 13 and 15 years-old, risk factors should be examined in detail. In this study, the primary goal of is evaluation of sociodemographic and clinical characteristics of juvenile offenders and the secondary goal is to examine the features that the clinician considers while setting up reports.Materials and Methods: Medical records of children dragged to crime aged between 13 and 15 years old were evaluated retrospectively. The sociodemographic characteristics of children and their parents’ crime type, crime story, family crime story and report result were included in the study.Results: The majority of cases (87.1%) were males. 31.7% of the cases left school. 55.4% were able to perceive the legal meaning and outcome of the crime and to direct their behavior. 43.6% had a mental disorder and the most common disorder was attention deficit hyperactivity disorder. The most common type of crime was wounding. 32.7% had repetitive crime stories. Both in the group that perceives the legal meanings and consequences of the crime and in the group of repetitive crime revealed statistically significant school failure, parental consanguinity, crime story in first-degree relative, cigarette/alcohol/substance abuse, and mental illness. Beck depression and trait anxiety scale (STAI-2) scores were higher in the group of repetitive crime. Theft (p=0.012) and battery crimes (p=0.046) tended to repeat more often.Discussion: Prominent risk factors in both criminal responsibility and repetitive crime groups are school failure, parental consanguinity, crime stories in relatives, cigarette/alcohol/substance abuse, and mental disorders. Although it is known that these risk factors may be a genetic ground, it is striking that many of them are features that can be prevented by protective and supportive studies. Social projects need to be developed for the children dragged to crime.
Keywords: child; delinquency; child psychiatry